A 150 MHz voltage controlled oscillator using lithium niobate RF-MEMS resonator - Kourani, Ali; Yong-Ha Song; Arakawa, Brandon; Ruochen Lu; Junfeng Guan; Anming Gao; Songbin Gong (2017 IEEE MTT-S International Microwave Symposium (IMS), 2017)
This paper presents the first radio frequency (RF) voltage controlled MEMS oscillator (VCMO) using a high Q Lithium Niobate (LiNbO 3 ) micromechanical resonator. The resonator has a quality factor of 650 in air with a motional impedance of 262 Ω. The oscillator's measured phase noise is -84.4 dBc/Hz and -146 dBc/Hz at 1 kHz and 1 MHz offsets respectively from a 149.13 MHz carrier with an output power of -8.6 dBm. The oscillator consumes less than 1 mA with a tuning range of 0.42 MHz. Such VCMOs are envisioned to enable low power, and low phase noise RF signal synthesis for Internet of Things applications.